Preexisting statin therapy is not associated with reduced acute kidney injury following cardiac surgery: a retrospective analysis - Wang, Jia; Huang, Chuzhu; Chen, Yan; Huang, Yilin; Wu, Zhuomin (Frontiers in Pharmacology, 2025)
BackgroundCardiac surgery-associated acute kidney injury (CSA-AKI) is one of the most prevalent forms of acute kidney injury (AKI) encountered in clinical practice, and its occurrence is significantly correlated with increased mortality and poor prognosis in patients. Although existing studies suggest that statins may influence the development of CSA-AKI through pleiotropic mechanisms, the findings from available studies and meta-analyses remain inconsistent. Therefore, the relationship between preexisting statin use and the risk of CSA-AKI development requires further investigation.MethodsThis study employed a retrospective cohort analysis based on the MIMIC-IV database. Patients undergoing ascending aortic surgery, coronary artery bypass grafting (CABG), or heart valve surgery were included and categorized based on preexisting statin use. Multifactorial logistic regression models were utilized to assess the association between statin use and outcome metrics, adjusting for confounding variables. To further validate the results, propensity score matching (PSM), sensitivity analyses, and subgroup analyses were conducted.ResultsA total of 4,783 patients were included, and the overall incidence of CSA-AKI was 30.02% (n = 1,436). Preliminary analysis showed that the incidence of AKI was significantly higher in the statin use group than in the non-use group (34.06% vs. 29.23%, P = 0.007). In the uncorrected model, statin use was associated with an elevated risk of AKI (OR = 1.25, 95% CI: 1.06–1.47); however, after multifactorial correction, the association was not statistically significant (OR = 1.00, 95% CI: 0.00-Inf, P = 1.000). Similarly, in the uncorrected model, statin use was associated with increased in-hospital mortality (OR = 1.28, 95% CI: 1.01–1.62) and ICU mortality (OR = 1.36, 95% CI: 1.07–1.72); however, after multifactorial correction, statin use was not significantly associated with in-hospital mortality (HR, 1.19; 95% CI, 0.92–1.53; P = 0.184) and ICU mortality (HR, 1.21; 95% CI, 0.94–1.55; P = 0.147) in the corrected model. PSM analysis (1:1 matching) further confirmed these findings (AKI: OR = 1.05, P = 0.621; in-hospital mortality: HR = 1.13, P = 0.438; ICU mortality: HR = 1.18, P = 0.299). None of the subgroup analyses (stratified by statin dose, AKI severity, and type of surgery) revealed significant interactions. Before PSM, no statistically significant differences were observed in 30-day (p = 0.126), 60-day (p = 0.372), or 90-day mortality (p = 0.652). After PSM, the mortality rates remained comparable between groups at all time points (30-day p = 0.297; 60-day p = 0.837; 90-day p = 0.966).ConclusionPreexisting statin use was not significantly associated with the risk of developing CSA-AKI, in-hospital mortality, or ICU mortality after appropriate correction for confounding variables. Similarly, no significant associations were observed for 30-day, 60-day, or 90-day mortality outcomes. Sensitivity analyses and subgroup analyses consistently supported this conclusion, suggesting that statin use may not significantly impact clinical outcomes in patients undergoing cardiac surgery.